PERBEDAAN KADAR ASAM URAT PADA WANITA PERIMENOPAUSE DAN MENOPAUSE - Patroni, Rini (Politeknik Kesehatan Kemenkes Bengkulu, 2017)
Increased levels of uric acid will occur in women after menopause due to a decrease in estrogen hormones that play an important role in increasing urinary acid excretion through urine. The occurrence of deposition of uric acid continuously in the body so that the kidneys are not able to remove uric acid properly. This study aims to determine differences in uric acid levels in perimenopausal women and menopause at Sukamerindu Health Center Bengkulu City. This study includes comparative study, with cross sectional study design. The sampling technique was purposive sampling as much as 74 respondents, with 37 respondents perimenopause women and 37 respondents of menopause women. Data analysis used univariate and bivariate analysis using independent t test. The mean rate of uric acid levels in perimenopausal women was 5.02 mg / dL while mean menopausal uric acid level was 7.04 mg / dL and after statistical test using independent t test, p value 0.0001, which means p <0, 05 then there are differences in uric acid levels in perimenopausal women and menopause at puskesmas sukamerindu city of Bengkulu. The average uric acid levels in menopausal women is higher compared with perimenopausal women so it is expected for menopausal women to maintain health and consume lots of mineral water so that uric acid does not accumulate in the body.